Management of Amniocentesis in High Risk Pregnancies and The Evaluation of the Results - Balcı, Osman; Acar, Ali; Çapar, Metin; Akyürek, Cemalettin; Durakbaşı, Gül; Zamani, Ayşegül; Acar, Aynur (Gynecology Obstetrics & Reproductive Medicine, 2006)
OBJECTIVE: To evaluate amniocentesis results applied to high risk pregnancies in our clinic. STUDY DESIGN: In this study, we have perf ormed amniocentesis in 16th-24th weeks of 447 pregnancies who had previous history of chromosomally abnormal fetus, high risk in triple test screening, in which abnomal fetus was seen in ultrasonography, high maternal anxiety, and maternal age 35 years old and above. Cytogenetic analyses were applied to all specimens. RESULTS: Appropriate amount of amniotic fluid was obtained by 98.65%, the successful culture rate was 97.31%, cardocentesis was applied to only one case of 12 cases in which no prolif eration was detected in culture The cordocentesis result was 47XX+18. According to cytogenetic evaluation results, chromosomal abnormality was detected in 29 cases (6.65%). In 7 patients Trisomy 21, in 3 cases Trisomy 18, in one case Trisomy 13, in 3 cases triploidy (69,XXX), in one case mosaicism (46XY/47XYY), in 5 cases translocation, in 9 cases inversion type chromosomal abnormality was detected. After 447 amniocentesis, 5 (1.11%) fetal losses developed. In 2 cases the leakage of amniotic fluid, in one case premature rupture of membranes, in one case cramps and vaginal bleeding and in only one case spontaneous abortus was detected. When the maternal educational level of the cases were evaluated, it was f ound that about one half of the cases had high level education. CONCLUSIONS: If amniocentesis is carried out by highly skilled physicians and if optimal culture conditions are available, amniocentesis is avaluable invasive prenatal diagnosis method with high accuracy and safety, with minimal complications.